Local authorities in the system of organs of state administration in forestry area of Ukraine: theoretic andlaw aspects - Печуляк, Віталій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article introduces theoretical and practical issues concerning participating of local authorities in state administration in the sphere of forestry. The article also points out the suggestions concerning improvement of the level of their efficiency and functioning.